VALORACIÓN DE LOS PRESAGIOS DE MUERTE EN LAS VIDAS DE LOS DOCE CÉSARES - Martínez Gázquez, José (Myrtia, 1988)
Suetonius' narrative technique arranges the elements of the report in consonance us the psychological and moral features which the personality and behavior of the characters described require. Moreover the emperors' destiny in the great beyond is partly implied by their death omens, which are closely related in the study to each emperor's past and moral characteristics. The exception of Galba can be explained by Suetonius' personal liking for him.